Analisis Psikologi Warna pada Ruang VIP Driving Range Jababeka Golf & Country Club - Zahra Amira Putri; Irma Damayantie (MAN 4 Kota Pekanbaru, 2026)
Interior design plays an important role in shaping corporate image and influencing users’ emotional experiences, particularly in premium sports facilities such as driving ranges. The VIP Room at Jababeka Golf & Country Club Driving Range is designed as a private training space that requires a high level of comfort, calmness, and focus. This study aims to analyze the application of color psychology in the interior design of the VIP Room based on Elliot’s Color-in-Context Theory (2015). The research adopts a qualitative-descriptive approach using a case study strategy, referring to the design process proposed by Rosemary Kilmer, which consists of analysis and synthesis stages. The unit of analysis consists of three VIP Room spaces within the driving range facility. Data were collected through field observations, visual documentation, and semi-structured interviews with management representatives and interior design stakeholders, supported by a literature review. Data analysis was conducted using thematic coding, focusing on the relationship between color application and users’ psychological responses. The results indicate that the dominance of green, combined with neutral tones and dark accents, creates psychologically stable and calming conditions that support user concentration. Furthermore, controlled color application reinforces the professional and exclusive image of the VIP Room, thereby enhancing the overall user experience.